2015
DOI: 10.5535/arm.2015.39.3.416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Epidural Electrical Stimulation and Repetitive Transcranial Magnetic Stimulation in Rats With Diffuse Traumatic Brain Injury

Abstract: ObjectiveTo evaluate the effects of epidural electrical stimulation (EES) and repetitive transcranial magnetic stimulation (rTMS) on motor recovery and brain activity in a rat model of diffuse traumatic brain injury (TBI) compared to the control group.MethodsThirty rats weighing 270-285 g with diffuse TBI with 45 kg/cm2 using a weight-drop model were assigned to one of three groups: the EES group (ES) (anodal electrical stimulation at 50 Hz), the rTMS group (MS) (magnetic stimulation at 10 Hz, 3-second stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…In the present study, neurobehavioral scores deteriorated following TBI. Nevertheless, we observed recuperation in the T + TMS group, in accordance with the findings of previous reports, which have indicated that functional and morphological changes occur after the application of extremely low-frequency electromagnetic fields [ 56 ], high-frequency rTMS [ 30 , 31 ], or repetitive transcranial direct current stimulation in a rat model of stroke [ 57 ]. Furthermore, the effect of magnetic fields in the reorganization of altered neural pathways is well-documented [ 58 , 59 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, neurobehavioral scores deteriorated following TBI. Nevertheless, we observed recuperation in the T + TMS group, in accordance with the findings of previous reports, which have indicated that functional and morphological changes occur after the application of extremely low-frequency electromagnetic fields [ 56 ], high-frequency rTMS [ 30 , 31 ], or repetitive transcranial direct current stimulation in a rat model of stroke [ 57 ]. Furthermore, the effect of magnetic fields in the reorganization of altered neural pathways is well-documented [ 58 , 59 ].…”
Section: Discussionsupporting
confidence: 92%
“…Yoon et al [ 32 ] observed an antiapoptotic effect around the perilesional area when high-frequency rTMS (10 Hz) was implemented starting 4 days after TBI in adult rats, although no functional improvements were observed. In contrast, other researchers have observed behavioral improvements in adult [ 30 ] and immature [ 31 ] rats subjected to TBI and treated with high-frequency rTMS (10 and 20 Hz, resp.) initiated at 1 day after TBI or 9 days after TBI, respectively.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The effects of epidural electrical stimulation (EES) and rTMS on motor recovery and brain activity were explored in a model of diffuse TBI (Yoon et al, 2015a). The rats were pre-trained to perform a singlepellet reaching task (SPRT) and a rotarod test (RRT) for 14 days.…”
Section: Animal Studiesmentioning
confidence: 99%
“…В них показан эффект применения ТМС в виде уменьшения апоптоза, увеличения нейрональной активности и повышения экспрессии маркеров нейропластичности [28][29][30]. Определенную настороженность вызывает описание индуцированных ТМС эпилептических приступов при лечении последствий ЧМТ, однако указывается, что данные приступы возникают при использовании высокочастотной стимуляции (>5 Гц), в то же время применение низкочастотной стимуляции считается безопасной методикой [31]. Значимое клиническое улучшение описано при применении ТМС у пациентов с последствиями легкой ЧМТ.…”
Section: травмы цнсunclassified